Chronic pain 1-5 years after heart transplantation-A nationwide cross‐sectional cohort study - Marita Dalvindt; Annika Kisch; Shahab Nozohoor; Annette Lennerling; Anna Forsberg (Wiley, 2020)
Abstract Aim To provide a multidimensional assessment of self‐reported chronic pain 1-5 years after heart transplantation and its relationship with self‐reported well‐being, fatigue, recovery, self‐efficacy and socio‐economic factors and to explore differences between heart recipients and a cohort of lung recipients. Design This multicentre, cross‐sectional, cohort study is a part of the Swedish national Self‐management after thoracic transplantation study. Methods Six questionnaires were distributed at the heart recipients yearly follow‐up (1-5 years) at three Swedish university hospitals 2014‐2017. Results The study group comprised of 79 heart recipients, 25 women and 54 men with a mean age of 52.68 years. Chronic pain among heart recipients was common and those not in paid employment as well as those with low psychological well‐being and high general fatigue reported significantly more pain. Female heart recipients were more affected by pain. General health and vitality, general fatigue, physical fatigue and reduced activity were related to the pain intensity score. Relevance to clinical practice As it is the duty of the healthcare system to provide adequate pain treatment, screening for pain should be a mandatory part of long‐term follow‐up.